ANALISIS EFEKTIVITAS PENAGIHAN PAJAK DENGAN SURAT PAKSA DAN KONTRIBUSINYA TERHADAP PENERIMAAN PAJAK PADA KANTOR SAMSAT GOWA - Darlini, Darlini; Nuhung, Mahmud; Salam, Abd (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2019)
The analytical method in writing this thesis is a quantitative descriptive method, which is an analysis that emphasizes the discussion of data and research subjects by presenting data systematically and not concluding the results of the study. In this study researchers used Quantitative Descriptive analysis techniques. This study aims to determine the level of effectiveness of tax collection by forced mail and its contribution to corporate income tax revenue at the Gowa Makassar Samsat office. From the results of the study it can be concluded that the collection of tax with a forced letter in the Gowa Makassar Samsat office is classified as Effective but the Tax Billing Contribution by forced letter to the tax revenue at the tax service office at Uptd Gowa Regional Income is classified as very less in terms of its nominal value.